The Impact of Péter Bod’s Translation of a Text about Galley Slaves - Gudor, Kund Botond (Acta Neerlandica, 2026)
Within his work on Protestant church history, Péter Bod’s translation of the galley slaves’history was one of those 18th century Protestant historiographical approaches, whichbound the image of the struggling Church to personal sacrifice for the true faith. In 1738,he translated Bálint Kocsi Csergő’s Narratio brevis, i.e. the history of the galley slaves’suffering, into Hungarian, entitled Siege of a House Built on a Rock. Although it was amanuscript, it became a bestseller copied and read all over the Carpathian Basin. Later,the image of the Protestant martyr was identified with what he delineated in his worksGod’s heroic Holy Mother Church and St. Heortocrat, namely, a martyr is an individualwho, in the midst of persecutions and fleeing, does not grow weary in being of use for thebenefit of his nation, his Church, the common good. In his works on church history, manyinventories of suffering from the 16th and 17th centuries demonstrate his utilitarian view ofmartyrdom. The secularized view of martyrdom identifies the notion of suffering forreligion with the struggle that he himself fought against the Habsburg censorship. The 17thand18th century Protestant history of suffering turned into an intellectual commitment thatis unfolding in the midst of difficulties and preserves our nationhood, and can be formedalong the jus and bonum publicum (public good, and public law).